Increased levels of Follicle Stimulating Hormone (FSH) and sertoli cells count in wistar rats induced with paraquat after green bean sprout extract supplementation - Auliya, Qurrotu A'yuni; Nasihun, Taufiqurrachman; Chodidjah, Chodidjah (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2022)
Paraquat herbicide disrupts the hormone Follicle Stimulating Hormone (FSH), causes testicular damage and changes in spermatogenesis. This study aims to determine the effect of supplementation of green bean sprout extract (Vigna radiata L.) on FSH levels, Sertoli cell counts in male Wistar rats (Rattus norvegicus) induced by paraquat herbicide. This research uses true experimental with posttest only control group design. A total of 25 rats were divided into 5 groups: P0 was given standard feed, P1 was given paraquat 4 4 mg/g BW, P2 was given green bean sprout extract supplement (GBES) dose 21.6 4 mg/g BW and paraquat 4 mg/g BW P3 was given GBES dose 43.2 4 mg/g BW and paraquat is administered orally for 15 days. Measurement of FSH levels using ELISA, while Sertoli cells were observed using testicular histology preparate. Mann-Whitney test resulted significance of p<0.05, which showed that the administration of GBES influenced FSH levels and the number of Sertoli cells. GBES doses of 21.6 4 mg/g BW, 43.2 4 mg/g BW, and 86.4 4 mg/g BW were shown to increase FSH levels and Sertoli cell counts in paraquat-induced Wistar rats. GBES increased FSH levels and the number of Sertoli cells in paraquat-induced rats.